2012
DOI: 10.1159/000334394
|View full text |Cite
|
Sign up to set email alerts
|

Adapted Timed Up and Go: A Rapid Clinical Test to Assess Gait and Cognition in Multiple Sclerosis

Abstract: Background/Aims: To measure the Timed Up and Go (TUG), imagined TUG (iTUG), and the difference of time between these two tests (delta time) in 20 patients with relapsing-remitting multiple sclerosis (RRMS) and 20 healthy age-matched controls and to examine whether an association with cognitive functions, motor impairment, and behavioral changes can be determined. Methods: The mean ± SD of TUG, iTUG and delta time were used as outcomes. Spatiotemporal gait parameters were recorded by a 12-camera optoelectronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
51
1
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(62 citation statements)
references
References 34 publications
7
51
1
3
Order By: Relevance
“…Both TUG and iTUG require cognitive and motor functions for their realizations and both have been correlated with these functions in previous studies [9][10][11]14] . TUG combines the 4 phases of sit-to-stand movement, initiation, acceleration and deceleration of gait, preparation of turning, turning and finally turning around to sit down [11] .…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…Both TUG and iTUG require cognitive and motor functions for their realizations and both have been correlated with these functions in previous studies [9][10][11]14] . TUG combines the 4 phases of sit-to-stand movement, initiation, acceleration and deceleration of gait, preparation of turning, turning and finally turning around to sit down [11] .…”
Section: Discussionsupporting
confidence: 53%
“…In schizophrenia, impaired TUG and iTUG were explained by alterations in executive function performances [10] . In relapsing-remitting multiple sclerosis, TUG was correlated with memory, attention and also with executive functions [11] . This study confirms the correlation between TUG and the ALSFRS-R shown by Montes et al [7] .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…It is currently unknown how muscle weakness affects STS movement mechanics for people with MS or the movement strategies people with MS use to perform the STS. Furthermore, prior investigations reporting leg strength deficits and slower movement times during the timed up and go and repeated STS movements have typically grouped all MS participants together regardless of leg strength (Allali et al, 2012;Dalgas et al, 2009). Not all persons with MS have leg strength deficits, and those who do not yet display leg weakness may not display the same STS movement mechanics or utilize the same movement strategies as persons with MS who have leg strength deficits.…”
Section: Introductionmentioning
confidence: 99%